PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SDN 138 KULINJANG - Suci Auliyah; Suparman; Suherman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Suci Auliyah (2026). The subjects of this study were 12 fourth-grade students of SDN 138 Kulinjangla Education Learning Outcomes of Fourth Grade Students of SDN 138 Kulinjang. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Enrekang, supervised by Dr. Suparman S.Pd., M.Pd and Suherman S.Pd., M.Pd.This study aims to improve students’ learning outcomes in Pancasila Education through the implementation of the Project Based Learning (PJBL) model for fourth-grade students at SDN 138 Kulinjang. The background of this research is based on the low learning outcomes of students, which are caused by teacher-centered learning methods, lack of variation in teaching models, and low student participation and motivation in the learning process. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 12 fourth-grade students of SDN 138 Kulinjang.